2021
DOI: 10.1111/ajt.16615
|View full text |Cite
|
Sign up to set email alerts
|

Reduced humoral response to mRNA SARS-CoV-2 BNT162b2 vaccine in kidney transplant recipients without prior exposure to the virus

Abstract: COVID‐19 is associated with increased morbidity and mortality in transplant recipients. There are no efficacy data available regarding these patients with any of the available SARS‐CoV‐2 vaccines. We analyzed the humoral response following full vaccination with the BNT162b2 (Pfizer‐BioNTech) in 136 kidney transplant recipients, and compared it to 25 controls. In order to exclude prior exposure to the virus, only participants with negative serology to SARS‐CoV‐2 nucleocapsid protein were included. All controls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
414
8
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 339 publications
(490 citation statements)
references
References 50 publications
(45 reference statements)
34
414
8
2
Order By: Relevance
“…Importantly, the authors reported no serious adverse events associated with the vaccine, and no event of graft rejection was observed. This is consistent with other early real-world reports in transplant recipients vaccinated with Moderna or BioNTech/Pfizer mRNA vaccines, in whom similarly no graft rejections were observed during the early follow-up period [5,6].…”
Section: Editorialsupporting
confidence: 92%
See 2 more Smart Citations
“…Importantly, the authors reported no serious adverse events associated with the vaccine, and no event of graft rejection was observed. This is consistent with other early real-world reports in transplant recipients vaccinated with Moderna or BioNTech/Pfizer mRNA vaccines, in whom similarly no graft rejections were observed during the early follow-up period [5,6].…”
Section: Editorialsupporting
confidence: 92%
“…The same group evaluated vaccine responses in 136 kidney transplant recipients (KTR) and reported even lower antibody responses following vaccination with BNT162b2 and only 37.5% of KTR had detectable SARS-CoV-2 specific antibodies [5]. Compared to LTR, seropositivity rates and mean antibody titers were lower in KTR [5], matching previous J o u r n a l P r e -p r o o f reports that transplant recipients other than LTR generally have a lower humoral response to vaccination [7]. This may be due to distinct immunosuppressive treatments used in different transplant groups.…”
Section: Editorialmentioning
confidence: 99%
See 1 more Smart Citation
“…Millions in the US alone suffer from either a primary or secondary immune deficiency; recent studies show that the majority of such patients mount insufficient response to vaccines. [11][12][13] Additionally, immunosenescence may . CC-BY-NC-ND 4.0 International license It is made available under a is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies from around the globe support the earlier findings that response to vaccines is low in the immunosuppressed, but the studies had small numbers of patients. [7][8][9] The second part of the Hopkins study showed slightly more promise after the second dose of the vaccine. 4 We still need more clinical data, but how quickly will it arrive?…”
Section: A Call For Research Shared Decision-making and Empowering Patients With Knowledgementioning
confidence: 99%